Teenage pregnancy and its consequences: Evidence from a South-eastern rural community of Nigeria - Grace Ifunanya Anayochukwu (Journal of Social, Humanity, and Education, 2022)
Purpose: This paper aims to investigate the relationship between education and teenage pregnancy, and its grave consequences on vulnerable teenagers. Methodology: A systematic random sampling method was used to select a sample of two hundred young teenagers from the eight villages that make up the Ihuokpara community. Frequency tables and pie charts were used for the analysis and interpretation of data, while chi-square (x2) was used in testing the hypothesis. Results: The findings revealed that teenage pregnancies occur as a result of a lack of education (Ignorance) about sexuality and other reproductive health-related issues. However, the findings also revealed that there is a water-tight relationship existing between education and the tide of teen pregnancy so that the rate of awareness of sexuality determines the rate of teenage pregnancy. Limitations: This study only examines some factors such as the low level of education (ignorance) about sexuality, human reproduction, sexual health, and other reproductive health-related issues that may cause teenage pregnancy in Ihuokpara. The future researcher may find other factors that are not included in this study. Contribution: This study hopefully can give some things that are important for the individual, family, and communities to lend their support to others in their articulated efforts toward the teenage pregnancy cases.